Alzheimer's elderly carrier and family caregiver: contributions from Imogene King's goal achievement theory (Research, Society and Development, 2022)
Objective: To reflect on the contribution of Imogene King's Goal Reach Theory in the construction of effective assistance to family caregivers of elderly patients with Alzheimer's. Methodology: Integrative literature review carried out in the following databases: SCIELO, BVS, LILACS and Medline/Pubmed based on studies available in English, Portuguese and Spanish, published between 2016 and 2021. Results: 19 articles that were relevant to this study were selected. revision. Among the neuropsychiatric symptoms presented by the elderly, apathy, anxiety and depression are the most frequent. Studies also point to loss of memory, language, cognitive functions, emotional and social control and loss of motivation. Caregivers of elderly people with Alzheimer's need professional health support, family organization, personal medical attention, and emotional support. It is important to encourage the caregiver's own well-being in order to guarantee and improve access to health care, prevent the functional decline of these caregivers, offering guidance on adequate care and with less risk. Care technologies adapted to the home environment and gerontotechnologies that directly contribute to care must be used, thus promoting informative and educational care. Conclusion: The family caregiver is the one who has the greatest contact with the elderly with Alzheimer's. In this sense, the Goal Attainment Theory proposed by Imogene King allows us to understand the impact of caring for patients with Alzheimer's on the family caregiver, their personal needs, as well as the strategies that can be used in order to achieve the goals established in the support to that caregiver.